1994
DOI: 10.2169/internalmedicine.33.540
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Systemic Lupus Erythematosus: A Report of an Autopsied Case.

Abstract: Anautopsied case of systemic lupus erythematosus with pulmonary hypertension is reported. A 29-year-old womanwith a seven-year history of polyarthralgia, butterfly rash, nephrotic syndromeand Raynaud's phenomenonwas admitted because of progressive dyspnea on exertion. Tests for antinuclear antibody, anti-cardiolipin antibody and lupus anticoagulant were positive. Echocardiographic examination revealed right ventricular hypertrophy and a moderate pericardial effusion. Estimated systolic pulmonary arterial press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…The clinical relevance of NYHA functional class, 6‐minute walking distance, and hemodynamics has been previously emphasized, since these are major end points in PAH and have a strong association with mortality (25). These results confirm and extend our previous data and case reports in the literature (13–18, 26, 27). Indeed, we recently reported that among 21 patients with SLE‐ or MCTD‐associated PAH, 8 (38%) were responders after at least 1 year of immunosuppressive therapy, without the need of addition of PAH‐specific therapy (20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The clinical relevance of NYHA functional class, 6‐minute walking distance, and hemodynamics has been previously emphasized, since these are major end points in PAH and have a strong association with mortality (25). These results confirm and extend our previous data and case reports in the literature (13–18, 26, 27). Indeed, we recently reported that among 21 patients with SLE‐ or MCTD‐associated PAH, 8 (38%) were responders after at least 1 year of immunosuppressive therapy, without the need of addition of PAH‐specific therapy (20).…”
Section: Discussionsupporting
confidence: 93%
“…The overexpression of growth factors such as platelet‐derived growth factors A and B and the chemokines RANTES/CCL5 and fractalkine/CX 3 CL1 have been demonstrated in the pulmonary arteries of patients with severe PAH (11, 12). These findings strongly support the use of immunosuppressants in CTD‐associated PAH, although conflicting results have been reported in the published case reports (13–19) and no randomized clinical trials have validated their use.…”
supporting
confidence: 53%
“…38 Plexogenic arteriopathy as a cause of pulmonary hypertension in SLE was described by Roncoroni, et al in 1992, 39 and later reported in other isolated cases. [39][40][41][42] We cannot assure that it is a sign of PHT, as it may be due to recurrent pulmonary thromboembolism or the presence of capillaritis. However, the absence of any marker of those primary events is highly suggestive of lupus-related PHT.…”
Section: Discussionmentioning
confidence: 99%
“…Of these four, three were "primary" non-thromboembolic PHT. Sato et al [41] in 1994 published an autopsied case of SLE complicated by primary PHT and aPL. There have also been other single case reports of patients with primary APS and this type of PHT [42][43][44][45].…”
Section: Pulmonary Hypertension and Antiphospholipid Antibodiesmentioning
confidence: 99%